The devil's wall : the nationalist youth mission of Heinz Rutha - Cornwall, Mark (Harvard University Press, 2012)
Heinz Rutha, pioneer of a youth movement that emphasized male bonding in its quest to reassert German dominance over Czechoslovakia, was arrested in 1937 for corrupting male adolescents. This led to an international scandal. Cornwall's biography is the first to tackle the long-taboo intersection of youth, homosexuality, and fascist nationalism.